PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII SMP ANGKASA LANUD SUTAN SJAHRIR PADANG - Sari, Yudia Mila (Jurnal Edukasi dan Penelitian Matematika, 2023)
The best problem-solving abilities should result from students' mathematical mastery. The class VIII pupils at SMP Angkasa Lanud Sutan Sjahrir Padang, however, only have rudimentary knowledge of how to solve mathematical problems, according to the results of the initial test. This is a result of the learning model being employed not prioritizing student learning (observation) and the fact that students are unfamiliar with problems that call for problem-solving (interview). A solution to these issues is provided by the problem-based learning (PBL) instructional model. This study sought to ascertain whether eighth-grade students at SMP Angkasa Lanud Sutan Sjahrir Padang are more adept at solving arithmetic problems while utilizing the Problem based learning learning model than when using the direct learning model. This study was a pseudo-experimental design with non-equivalent posit test and only one control group. Students in the 8th grade at SMP Angkasa Lanud Sutan Sjahrir Padang Academic Year 2022/2023 served as the study's sample. In a straightforward random sampling method used to choose research samples, class VIII.1 serves as the experimental class and class VIII.2 serves as the control class. The P-value = 0.002 was found with a significant level (? = 0.05) based on the analysis of the test results for mathematical problem-solving skills. As a result, H0 is disregarded. Problem based learning learners in the eighth grade perform mathematical problem solving tasks more effectively than direct learners.Keywords- Problem based learning, Problem solving